The pathway to residency in Germany: a survey study to identify factors that impact an international medical graduate from Syria - Saadoun, Rakan; Risse, Eva-Maria; Sadoun, Leen; Surucu, Yusuf; Bittar, Ranim; Heshma, Mhd Anas; Obermueller, Theresa (BMC medical education, 2022)
The German health care system has recently become an attractive destination for international medical graduates, particularly from developing countries such as Syria. However, there are no studies about the factors that influence the successful entry into the German healthcare system at trainee level.